NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI SEDEKAH LAUT MASYARAKAT PESISIR KELURAHAN PALABUSA KECAMATAN LEA-LEA KOTA BAUBAU - Dermawan; Sulasri; Darmayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the values of Islamic education embedded in the sedekah laut (sea almsgiving) tradition of the coastal community in Palabusa Village and to analyze Islamic perspectives and community responses toward the tradition. This research employed a qualitative approach with an ethnographic design, collecting data through participant observation, in-depth interviews, and documentation. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, with validity tested through source and technique triangulation. The findings reveal that the sedekah laut tradition contains four Islamic educational values manifested concretely throughout its stages, namely the value of gratitude as a reflection of tawhid, the value of mutual cooperation as an expression of social ethics, the value of brotherhood built through togetherness across all social strata, and the value of cultural preservation as a moral responsibility across generations. Community perspectives on the tradition are divided between those who accept it as an Islamic-compatible practice and those who advocate for adjustments to certain ritual elements to better align with Islamic law. Nevertheless, the community of Palabusa collectively agrees to preserve this tradition as a culturally valuable identity. This research contributes to the development of character education based on local wisdom, relevant to the achievement of SDGs goals 4 and 11.